Investigation on drug dosage form : analysis of prescriptions available in pharmacy in kotamadya Yogyakarta - Chairun Wiedyaningsih; Oetari . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The analysis of dispensing prescriptions available in Pharmacy in Yogyakarta was performed. The analysis included observation problems of dosage form preparations, and examination compounds of medicines which were mentioned in dispensing prescriptions. The study was conducted by sampling dispensing prescriptions from the pharmacy located in Yogyakarta. Questionnaires and interviews to pharmacists were also conducted in order to support the prescription data. The result showed that the oral solid dosage forms were the majority (71%) of dispensing prescriptions written. tablet crushing was the major problems of. The majority objective of therapy with this type of dispensing were for asthma, infection and allergy. It was also found that brand names (74%) medicine were more written than generic names. The most generic name written/added was CTM (chlorpheniramin maleat). Results of questionnaire evaluation showed that semi solid (unguentum, cream) was the major problem (69%) of pharmaceutical dispensing in the Pharmacy. Dispensing Salicylic acid with other semi solids were the most problems. Prescription analysis showed that about 14,2% dispensing prescriptions contain salycilic acid mixed with cream, and 26,5% dispense prescriptions contains salicylic acid mixed with any kinds of drugs or other semi solid forms. Liquid were the minor (7,2%) dispensing prescriptions written by physicians. However problems were still remain caused bycrushing coated tablets and dispensing to the liquid.Keywords : prescription, pharmaceutical stores, dosage forms, Yogyakarta